2022
DOI: 10.7759/cureus.22730
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Cholesteatoma: Typical Findings and Evaluation of Diagnostic Utility on High Resolution Computed Tomography

Abstract: BackgroundPre-operative assessment of middle ear cholesteatoma is a must for assessing the disease's location, extent, and complication, and high-resolution computed tomography (HRCT) is the modality of choice. Therefore, this study aims to assess the common signs of cholesteatoma on HRCT and its diagnostic ability. MethodsFifty patients with suspected cholesteatoma were considered for the study, which was carried out on an Ingenuity Core 128 slice CT scanner (Philips, Amsterdam, Netherlands). The bilateral te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In our study, we found four cases (9%) of an LSC fistula. Other studies noted an LSC fistula in just 4.7% of the cases and even lower (4% of the patients) [16,28]. In our study, HRCT scans assessed the LSC fistula cases with a sensitivity of 75% and specificity of 97.6%.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In our study, we found four cases (9%) of an LSC fistula. Other studies noted an LSC fistula in just 4.7% of the cases and even lower (4% of the patients) [16,28]. In our study, HRCT scans assessed the LSC fistula cases with a sensitivity of 75% and specificity of 97.6%.…”
Section: Discussionmentioning
confidence: 46%
“…Also commonly detected was the pars flaccida type [12]. In other studies, the most frequently encountered type was pars flaccida cholesteatoma: a study on 30 cholesteatoma cases showed lesions in the epitympanum in 73.3% of patients, followed by mesotympanum [15], and in another one pars flaccida cholesteatoma was described in 50.7% of cases, followed by extensive cholesteatoma in 30.1% of patients [16]. Pars tensa cholesteatoma was the least encountered type in most of the studies.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Offering a cost-effective alternative to magnetic resonance imaging (MRI), CT is instrumental in distinguishing cholesteatoma from CSOM by detecting osseous erosion in the tympanum. Although studies have shown that clinicians are capable of diagnosing COM based on CT alone [11][12][13][14][15][16][17], distinguishing between COM subtypes poses greater challenges to the human eye.…”
Section: Introductionmentioning
confidence: 99%